Andean Pedagogy and Curriculum for Knowledge - Vásquez Carrillo, Francisco (2022)
Half a millennium after the independence of the Latin American countries (Andean-Anahuac), the ministries of education imitate, adopt and adapt pedagogical approaches and currents from Europe and the United States, thus underestimating the historical  richness of their peoples; they apply decontextualized principles and theories. On the other hand, it is notorious the anomie from the educational systems to respond to the crisis of anthropocentric instrumental rationalism, which has placed humanity before an imminent socioeconomic and ecological catastrophe. Faced with this situation, a pedagogy rooted in a millenary Andean cultural historical tradition is proposed. The fabric of Andean Thought affirms a cosmocentric vision, from epistemic, ontological and axiological bases, which we will call Andean Pedagogy. The Cosmo-Pedagogy or Andean Pedagogy enables the framework of an educational curriculum based on knowledge, equidistant from Western pedagogics, such as the competency approach. AndeanPedagogy is based on the principles of Andean Thought strengthened by philosophy, history, anthropology, archeology, sociology and psychology. The research corresponds to the descriptive bibliographic method.